Elephants cannot dance! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2009)
Piggy loves to dance and wants to teach everyone, including her best friend, Gerald the elephant.
0.9
K-3.
K-3
Keywords: Dance -- Juvenile fiction; Elephants -- Juvenile fiction; Swine -- Juvenile fiction; Dance -- Fiction; Elephants -- Fiction; Pigs -- Fiction; Dance -- Fiction; Elephants -- Fiction; Pigs -- Fiction; Humorous fiction; Readers (Publications)